The Effect of Using High Dose Simethicone on the Visibility of Upper Gastrointestinal Endoscopy - Dangprasert, Somsak (Health Science Clinical Research, 2020)
Object: This study aimed to evaluate the efficacy of using 80 mg compare to 240 mg of simethicone and no medication on the visibility in Esophagogastroduodenoscopy (EGD) Study Design: A randomized single blinded (physician) control study Methods: 141 patients were randomized to 3 groups. The control group (groupA) was prepared by no medication. The experimental groups were prepared by simethicone 80 mg (groupB) and 240 mg (group C) 15-30 minutes before underwent EGD by single surgeon. Study endoscopist was blinded to group allocation. Data were collected by using record form for evaluate 1.) mucosal visibility at 4 locations (lower esophagus, upper stomach, antrum, 1st and 2nd part duodenum) by using total mucosal visibility score (TMVS) 2.) procedure time 3.) volume of fluid flush required to achieve adequate mucosal view. The data were analyzed by ANOVA test. Results: 1.) Both simethicone groups (group B and C) had significantly better mean TMVS (TMVS group A=7.67, group B=5.43, group C=5.43) compared to control group A (p<0.001) but not significantly different between group B and C (P=0.337) 2.) Both simethicone groups (group B and C) had significantly shorter procedure time (group A=237.87 seconds, group B=190.02 seconds, group C= 187.67 seconds) compared to control group A (p<0.001) but not significantly different between group B and C (P=0.620) 3.) Both simethicone groups (group B and C) had significantly less volume of fluid flush required to achieve adequate mucosal view (group A=82.61ml, group B=27.17ml, group C =16.33 ml) compared to control group A (p<0.001) but not significantly different between group B and C (p=0.475) Conclusions: By using simethicone 80 mg 15-30 minutes before underwent EGD had increased mucosal visibility, shortened procedure time and less volume of fluid flush required to achieve adequate mucosal view compared to control group. But increasing dosage of simethicone 240 mg had not different to 80 mg. Keywords: Simethicone, Esophagogastroduodenoscopy, Mucosal visibility